Application of Anthocyanin Extract from Purple Sweet Potato (Ipomoea batatas L.) as a Natural Indicator for Borax Detection in Puli Crackers - Zaenab, Zaenab (Journal of Public Health and Pharmacy, 2026)
Introduction: Food safety remains a major public health concern because contaminated food may cause adverse health effects, including poisoning from prohibited additives such as borax. Borax is illegally added to improve texture and shelf life despite its known toxicity. Puli crackers, a traditional snack widely consumed in Makassar City, are suspected of containing borax. This study aimed to detect borax in puli crackers using anthocyanin extract from purple sweet potato (Ipomoea batatas L.) as a natural colorimetric indicator. Methods: This research employs an observational method with a descriptive approach. A total of 21 puli cracker samples were purposively collected from five production sites and 16 street vendors. Samples were aseptically packaged in sterile polyethylene bags, labeled, and transported to the laboratory within 24 hours. In the laboratory, samples were homogenized, and aliquots were subjected to qualitative colorimetric analysis using anthocyanin extract to detect the presence of borax based on observable color changes. Borax detection was performed at the Chemistry Laboratory of Poltekkes Kemenkes Makassar using filter paper infused with purple sweet potato anthocyanin extract. A standardized borax test kit was used as a confirmatory method. Results: All samples tested positive for borax, indicated by bluish-green to blue color changes and confirmed by the test kit. Sample pH values ranging from neutral to alkaline (7–9), with alkaline values supporting borax presence, with alkaline values supporting borax presence. Conclusion: The findings highlight the urgent need for stricter regulatory monitoring of food production and distribution by relevant authorities. Enhanced education and outreach to producers and street vendors regarding the health risks of borax are also essential. Consumers are encouraged to be more vigilant in selecting food products and to recognize signs of potential borax contamination to reduce exposure risks.